Success factors for creating a PMO aligned with the objectives and organizational strategy - Abad Espinoza, M. (2010)
This article deals with how to implement a Project Management Office that is aligned with the objectives and organizational strategy. This study documents the experience provided by the implementation of a PMO at the Department of Technology at the Universidad Técnica Particular de Loja, which methodology for managing projects was evolved from a documented oriented version to a deliverable oriented process. This study highlights the relevant aspects for setting up a functional PMO, which adds value to the organization.